Optimization of sugarcane farming as a multipurpose crop for energy and food production. Issue 1 (25th March 2014) - Sabatier, Damien; Martiné, Jean‐François; Chiroleu, Frédéric; Roussel, Camille; Letourmy, Philippe; van Antwerpen, Rianto; Gabrielle, Benoit; Ney, Bertrand
Abstract Sugarcane is a multipurpose crop whose components may be used, in addition to sugar production, for various energy carriers or end‐products (electricity, liquid biofuels and heat) which enhance its economic potential. For many years, plant breeders and agronomists have focused on increasing sucrose yields per hectare and millers on increasing recoverable sucrose per ton of sugarcane in sugar mills. Attempting to exploit the energy potential of sugarcane more fully, calls for a more holistic approach focusing on both sucrose and lignocellulosic components of sugarcane biomass, and gaining some insight into the management practices required to optimize sugarcane cropping systems in these respects. Such options include genotype selection, harvest date with respect to the crop's growing cycle, crop type (plant crop vs. ratoon crops) and harvesting systems (mechanical vs. manual). The effects of these factors are strongly modulated by climate and soil properties, and these interactions are overall poorly known. Here, we set out to examine sugarcane infield management × environmental interactions with respect to (i) sugarcane yield and partitioning of the aboveground biomass; and (ii) sugarcane milling products (recoverable sucrose yield and amounts of coproducts) and their derived energy carriers. Three Saccharum cv. cultivars (R570, R579 and R585) were planted in three locations on La Reunion Island with contrasting management practices and climatological conditions. Quality characteristics of the samples were assessed by conventional and near infrared spectroscopy methods. Product, coproducts and potential energy production were measured and computed using transfer equations and a mill‐operating model. Yields and quality characteristics from cultivars and harvesting systems were affected differently by environmental factors – low temperature and radiation, and water stress. The current study also provides valuable information on how combinations between environments, genotypes and practices affect yield and partitioning of the aboveground biomass, and food and energy production.